A test of the 2 × 2 Model of Perfectionistic Pressure in youth sport - Fleming, D. J. M.; Madigan, D. J.; Mallinson-Howard, S. H.; Hill, A. P. (Psychology of Sport and Exercise, 2023)
Perfectionistic pressure from coaches and parents is likely to contribute to the development of perfectionism in youth athletes. However, if and how perfectionistic pressure from coaches and parents interact to predict the development of perfectionism is unknown. With this in mind, the present study tested a new model - the 2 × 2 Model of Perfectionistic Pressure - that focuses on the different combinations of perfectionistic pressure youth athletes can experience. Four within-person combinations of perfectionistic pressure are identified and compared: Pure coach pressure (high coach pressure/low parental pressure), pure parental pressure (low coach pressure/high parental pressure), mixed pressure (high coach pressure/high parental pressure), and low pressure (low coach pressure/low parental pressure). To test the model, a sample of 210 youth athletes (M age = 14.68 years) completed measures of perfectionistic strivings, perfectionistic concerns, coach pressure to be perfect, and parental pressure to be perfect. Moderated hierarchical regression and simple slopes analyses revealed that mixed pressure was related to the highest levels of both perfectionistic strivings and perfectionistic concerns. The findings provide initial evidence for the new model and suggests it will be useful in studying the development of perfectionism and other outcomes in sport.